PARADIGMA POLITIK HUKUM PENGUPAHAN INDONESIA: STUDI HAK ATAS UPAH LAYAK BAGI BURUH INFORMAL - Syahwal Syahwal (Faculty of Law, Parahyangan Catholic University, 2023)
In developing countries, including Indonesia, majority of workers are informal with low wages. This situation occurs mainly because of the problems with their status as informal workers and how Indonesian labor law regulates on that matter. On this basis, this research was conducted by investigating labor law policies in the field of wages that do not protect informal workers, i.e., wage policy. There are two issues that are the focus of the study in this research. The first is: what is the paradigm of Indonesian wage policy? Second, what paradigm must be incorporated into wage policy in order to provide informal workers with decent wages? The research was conducted using a non-doctrinal research type supported by statutory and conceptual approaches. The conceptual approach is particularly based on Roscoe Pound’s conceptualization of sociological jurisprudence. The research resulted in the finding that Indonesian wage policy is based on the contractualism paradigm, which is rooted in the idea of neoliberalism and causes informal workers to receive low wages. The study also reveals that there is a need to incorporate a human rights paradigm into Indonesian wage policy so that Indonesian wage policy is able to provide a decent life for informal workers.